Emerging Trends in Children’s Literature: Editor’s Perspective - Sutar, Bijnan (THE PRIMARY TEACHER, 2019)
The literature or reading material available for one’s consumption as a bibliophile is the most important resource of a community/nation. The progress in technology has enhanced its quality and quantity towards getting a broader appeal and wider reach respectively. This growth in terms of variety and ease of availability has enriched our community and its children, the future citizens. The knowledge, now is not only restricted to the prescribed syllabus for children but also goes beyond the textbooks and to the realm of their inquisitiveness and interest. Literature aspiring for reach not only fly clasping the wings of books but also spread their span of flight flowing along with the newest media of digital world. This amalgamated medium of dissemination is the golden path to the readers, overcoming various barriers. We will understand the gradual progress of publishing in the last three decades.